Supercritical carbon dioxide extracts of small cardamom and yellow mustard seeds have fasting hypoglycaemic effects: diabetic rat, predictive iHOMA2 models and molecular docking study. Issue 4 (28th February 2021) - Paul, Kaninika; Chakraborty, Soumi; Mallick, Priyanka; Bhattacharjee, Paramita; Pal, Tapan Kumar; Chatterjee, Nilendra; Chakrabarti, Saikat
Abstract: In the present investigation, the supercritical carbon dioxide (SC-CO2 ) extracts of small cardamom (SC) and yellow mustard (YM) seeds have been investigated for their efficacies in combating type 2 diabetes in streptozotocin-induced Wistar albino rats. Fasting blood glucose (FBG) levels in the rats were monitored on days 8, 15 and 21. On day 15, FBG level reduced appreciably by 31·49 % in rats treated with SC seed extract and by 32·28 % in rats treated with YM seed extract, comparable to metformin (30·70 %) and BGR-34 (a commercial polyherbal drug) (31·81 %) administered rats. Either extract exhibited desirable effects on hepatic glucose-6-phosphatase, glucose-6-phosphate dehydrogenase (G6PD) and catalase activities in controlling diabetes. A molecular docking exercise was conducted to identify specific compounds in the extracts which possessed augmenting effect on G6PD. The results revealed that all the bioactive compounds in the extracts have binding affinities with the enzyme and contributed to the antidiabetic efficacies of the extracts as G6PD augmenters. The effects of the extracts on insulin sensitivity and glucose uptake were investigated using non-invasive modelling by iHOMA2 software. This in vitro approach indicated that extract administration resulted in increased both insulin sensitivity of the liver and glucose uptake in the gut. The findings of the present study attest these SC-CO2 extracts of the spices as safe alternatives of metformin and BGR-34 in combating type 2 diabetes and could be safely subjected to clinical studies. These extracts could also be employed in designing proactive food supplements in mitigating the metabolic disorder.